2015
DOI: 10.3835/plantgenome2014.10.0065
|View full text |Cite
|
Sign up to set email alerts
|

High‐Density Single Nucleotide Polymorphism Linkage Maps of Lowland Switchgrass using Genotyping‐by‐Sequencing

Abstract: Switchgrass (Panicum virgatum L.) is a warm-season perennial grass with promising potential as a bioenergy crop in the United States. However, the lack of genomic resources has slowed the development of plant lines with optimal characteristics for sustainable feedstock production. We generated high-density single nucleotide polymorphism (SNP) linkage maps using a reducedrepresentation sequencing approach by genotyping 231 F 1 progeny of a cross between two parents of lowland ecotype from the cultivars Kanlow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 110 publications
0
24
0
Order By: Relevance
“…The QTL on LG 1b co-localizes with QTL for base tiller width, internode width, and fourth leaf length and area that we detected in parallel experiments using ALB [49]. It was a result of segregating variation in Kanlow-K5, in a region of the genome that is covered by maps for both parents [42,47]. By contrast, the QTL we detected for LMA at 146 cM on LG 5b is novel, and segregation from Alamo-A4 was implicit in its location: in the original male and female maps for ALB that our map is derived from, no information was available for the Kanlow-K5 (female) parent beyond 84 cM of LG 5b [47].…”
Section: Quantitative Trait Locimentioning
confidence: 52%
See 2 more Smart Citations
“…The QTL on LG 1b co-localizes with QTL for base tiller width, internode width, and fourth leaf length and area that we detected in parallel experiments using ALB [49]. It was a result of segregating variation in Kanlow-K5, in a region of the genome that is covered by maps for both parents [42,47]. By contrast, the QTL we detected for LMA at 146 cM on LG 5b is novel, and segregation from Alamo-A4 was implicit in its location: in the original male and female maps for ALB that our map is derived from, no information was available for the Kanlow-K5 (female) parent beyond 84 cM of LG 5b [47].…”
Section: Quantitative Trait Locimentioning
confidence: 52%
“…By contrast, the QTL we detected for LMA at 146 cM on LG 5b is novel, and segregation from Alamo-A4 was implicit in its location: in the original male and female maps for ALB that our map is derived from, no information was available for the Kanlow-K5 (female) parent beyond 84 cM of LG 5b [47]. Interestingly, the tip of LG 5b is also not covered in the NF × GA map [56], more recent genotyping-by-sequencing maps for ALB [42] or a novel four-way cross that incorporates the Alamo-AP13 genotype as a male parent [45]. These results suggest that there may be a low level of polymorphism in the genome of cv.…”
Section: Quantitative Trait Locimentioning
confidence: 95%
See 1 more Smart Citation
“…Single nucleotide polymorphisms (SNPs) are mutations that occur between the genomes of related organisms, and are commonly used as molecular markers for genetic research (Fiedler et al 2015; Mammadov et al 2012; Vignal et al 2002; Wang et al 1998; Yang et al 2010). Genotyping-by-sequencing described by Elshire et al (2011) can produce thousands of SNPs, which may be more capable of elucidating differences among bermudagrass cultivars within the Tifgreen mutation family (Elshire et al 2011; Poland et al 2012; Poland and Rife 2012).…”
Section: Advances In Molecular Marker Technology For Evaluating Bermumentioning
confidence: 99%
“…Genotyping-by-sequencing described by Elshire et al (2011) can produce thousands of SNPs, which may be more capable of elucidating differences among bermudagrass cultivars within the Tifgreen mutation family (Elshire et al 2011; Poland et al 2012; Poland and Rife 2012). Fiedler et al (2015) and Poland and Rife (2012) suggested that GBS offers the potential to identify sets of closely linked loci that contribute to phenotypic variation. The ability to connect phenotype to genotype is of great value to researchers to gain a better understanding of the development and progression of bermudagrass cultivars used on golf course putting greens.…”
Section: Advances In Molecular Marker Technology For Evaluating Bermumentioning
confidence: 99%